Dual-Energy Semiconductor Detector of X-Rays and Gamma Radiation - Brodyn, M.S.; Vesna, V.T.; Degoda, V.Ya.; Zaitsevskiy, I.L.; Kozhushko, B.V. (Science and Innovation, 2024)
The major types of ionizing radiation detectors, their advantages and disadvantages have been analyzed. The application of ZnSe-based semiconductor detector in high temperature environment has been substantiated. Original ZnSe-based detectors and a double-chip design for registration of X- and gamma rays have been used in a broad energy range. Based on the manufactured simulator, the feasibility of gamma quanta recording by a high-resistance ZnSe-based detector operating in perpulse mode has been proved.